2015
DOI: 10.1007/s11746-015-2660-1
|View full text |Cite
|
Sign up to set email alerts
|

Prosopis farcta Seeds: Potential Source of Protein and Unsaturated Fatty Acids?

Abstract: The goal of this study is to evaluate the chemical composition of the Prosopis farcta seeds. The Kjeldahl method revealed that the level of the total protein was ca. 18 % on a dry weight basis (DW). Gas chromatographic analysis revealed the presence of six fatty acids. Linoleic acid with 57.55 % was the major fatty acid, followed by oleic and palmitic acids (24.58 and 12.91 %, respectively). Total phenolic content was 1.71 mg GAE/g DW (GAE = gallic acid equivalents). Methanolic extracts showed important antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Indeed, previous studies on numerous plantseeds have suggested the effect of the environmental conditions (precipitation and temperature) on the composition of the fatty acids. Aslam et al (2009), Schulte et al (2013) and BenLajnef et al (2015) have reported the effect of temperature and precipitation on palmitic acid, oleic acid and linoleic acid composition, which support our findings. Youzbachi et al (2012) have suggested that in 12 Tunisian A. cyanophylla, linoleic acid (61.11-65.45%) and oleic acid (19.67-22.85%) are the major fatty acids.…”
Section: Fatty Acids Compositionsupporting
confidence: 88%
“…Indeed, previous studies on numerous plantseeds have suggested the effect of the environmental conditions (precipitation and temperature) on the composition of the fatty acids. Aslam et al (2009), Schulte et al (2013) and BenLajnef et al (2015) have reported the effect of temperature and precipitation on palmitic acid, oleic acid and linoleic acid composition, which support our findings. Youzbachi et al (2012) have suggested that in 12 Tunisian A. cyanophylla, linoleic acid (61.11-65.45%) and oleic acid (19.67-22.85%) are the major fatty acids.…”
Section: Fatty Acids Compositionsupporting
confidence: 88%
“…23 Oil extracted from seeds was analyzed and found containing a high concentration of protein (18%), unsaturated fatty acids (UFA) and low total phenolic content (1.7 mgGAE g -1 ). 24 Aqueous extract of dry aerial parts was prepared and total phenolic content was measured and found 17.3 mgGAE g -1 . 25 HPLC analysis of acetone and methanol (successively) extract of different parts of the plant, harvested from various locations.…”
Section: Methods and Findingsmentioning
confidence: 99%
“…Highly active. 24 Aqueous extract of aerial parts was tested with FRAP and ORAC methods and found moderately active. 25 Various extracts of aerial parts (including ultra-sonic assisted) were prepared and tested for antioxidant activity (DPPH): moderate.…”
Section: Antioxidantmentioning
confidence: 99%
“…respectively for the n-hexane, methylene chloride, ethyl acetate and n-butanol extracts compared to ascorbic acid as standard (89.2%). The IC 50 value of the ABTS free radical activity of the methanol extract of P. farcta fruits growing in Tunisia was 270 μg/ml (Lajnef et al, 2015). To the best of our knowledge, there are limited reports about the antioxidant activity of P. farcta using the ABTS assay, but there are available data about other assays that is, the antioxidant activity of four solvent extracts from pod and seed of P. farcta was evaluated using DPPH assay, and the IC 50 of the tested extracts from pod part were 1.0, 6.15, 3.55 and 7.75 µg/ml respectively for ethanol, methanol, octanol and n-heptane extracts, while and the IC 50 of the tested extracts from seed part were 2.0, 1.51, 0.95 and 4.45 µg/ml respectively for ethanol, methanol, octanol and n-heptane extracts (Poudineh et al, 2015).…”
Section: Free Radical Scavenging Antioxidant Activity (Abts Assay)mentioning
confidence: 97%
“…(Family Fabaceae) is a little prickly spiny shrub; it is native of United States, Kuwait, Turkey, Iraq, Iran, Northern Africa, and South Western Asia (Sharifi-Rad et al, 2014). Different phytochemicals were reported to be isolated and identified from the plant viz., volatile constituents (Harzallah-Skhiri et al, 2006), proteins and unsaturated fatty acids (Lajnef et al, 2015), and flavonoids (Direkvand-Moghadam et al, 2014). A literature survey revealed that P. farcta has been used in the treatment of neurological disorders (Mollashahi et al, 2013) and cholesterol level (Omidi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%